Debate effectiveness for the strengthening the university educational work from the curricular work - Julio Fragoso Fragoso; Blanca Rosa Garcés Garcés; Lian Roque Roque; Ibys Espinosa Requesens; Valia Caminero Chávez; Francisco Jacas Frada (Medisur, 2017)
Foundation: The well-conceived debate can strengthen the university educative influence from the curricular work, but the strategies designed for citizen training in the universities privilege the professional to the detriment of training them to social reality questioning. Objective: To demonstrate the effectiveness of the debate for the strengthening of university educative influence from the curricular work. Methods: Pedagogical research carried out at the University of Medical Sciences of Cienfuegos, from September 2016 to January 2017, with the Philosophy class in the first year of the Dentistry Major. The debate deliberated by the teacher was introduced on the basis of articles with impact on the current Cuban society, previously selected and student oriented. It was considered as a requirement that the student had possibilities of a previous preparation before the debate. Two measurements were taken, one in November and another at the end of the semester. A survey was applied that measured: students 'satisfaction with the method used, students' perception about the contribution to the formation of values. Results: All the students are satisfied by the method used; At the end of the semester 77, 8 % of the students considered that the method contributes to the formation of values and reinforcement of patriotic feelings in them. Conclusion: Offering students the possibility of confronting different opinions is possible if a relaxed and rewarding climate is achieved. It is corroborated that the work of the teacher is irreplaceable at university formation from the curricular work of each discipline.